Long‐term results of ileal ureteric replacement: a 25‐year single‐centre experience. (21st March 2017) - Kocot, Arkadius; Kalogirou, Charis; Vergho, Daniel; Riedmiller, Hubertus
Abstract : Objective: To report the long‐term outcomes of ileal ureteric replacement (IUR) in complex reconstruction of the urinary tract. Patients and Methods: From 1991 to 2016, IUR was performed in 157 patients with structural or functional ureteric loss. In 52 patients, bilateral IUR became necessary. Implantation sites where either the native urinary bladder ( n = 79) or intestinal reservoirs ( n = 78). In the latter group, the technique was used at the time of primary urinary diversion ( n = 34), in a secondary approach ( n = 29), and in undiversion or conversion procedures ( n = 15). Anti‐refluxive implantation was performed in 37 patients. In eight patients the ileal ureter was implanted into the cutis as an ileal conduit. All patients were followed prospectively according to a standardised protocol. Results: The mean follow‐up was 54.1 months. In 114 patients with dilatation of the upper urinary tract before surgery a significant improvement of the dilatation was confirmed in 98 patients. Serum creatinine levels decreased or remained stable in 147 of the 157 patients. Reflux was present in all cases without and in six cases with an anti‐reflux mechanism. In six patients, operative revision became necessary because of severe metabolic acidosis, mucus obstruction or stenosis of the ileal ureter. Conclusions: To our knowledge, this is the world's largest single‐centre series of IUR reported to date. Long‐term follow‐up confirms that this approach is a safe and reliable solution, even under complex conditions. Anti‐refluxive implantation is recommended for intestinal reservoirs, whereas reflux prevention seems to be of minor importance when the native bladder is chosen as the site of implantation.